Core‐shell structured P2‐type layered cathode materials for long‐life sodium‐ion batteries - Huili Wang; Jianing Qi; Peixin Jiao; Zhonghan Wu; Ziheng Zhang; Na Jiang; Dongjie Shi; Geng Li; Zhenhua Yan; Kai Zhang; Jun Chen (SmartMat)
Abstract P2‐type layered Ni–Mn‐based oxides are vital cathode materials for sodium‐ion batteries (SIBs) due to their high discharge capacity and working voltage. However, they suffer from the detrimental P2 → O2 phase transition induced by the O2−−O2− electrostatic repulsion upon high‐voltage charge, which leads to rapid capacity fade. Herein, we construct a P2‐type Ni–Mn‐based layered oxide cathode with a core‐shell structure (labeled as NM–Mg–CS). The P2‐Na0.67[Ni0.25Mn0.75]O2 (NM) core is enclosed by the robust P2‐Na0.67[Ni0.21Mn0.71Mg0.08]O2 (NM–Mg) shell. The NM–Mg–CS exhibits the phase‐transition‐free character with mitigated volume change because the confinement effect of shell is conductive to inhibit the irreversible phase transition of the core material. As a result, it drives a high capacity retention of 81% after 1000 cycles at 5 C with an initial capacity of 78 mA h/g. And the full cell with the NM–Mg–CS cathode and hard carbon anode delivers stable capacities over 250 cycles. The successful construction of the core‐shell structure in P2‐type layered oxides sheds light on the development of high‐capacity and long‐life cathode materials for SIBs.